Archival Supervision Effectiveness in Digital Government Era: Evidence from Riau Islands Province - R. Rahmat; Edy Akhyary; Dedy Afrizal (Golden Ratio of Social Science and Education, 2026)
This study examines the performance of internal archival supervision within the Riau Islands Provincial Government amid digital archival transformation. Although archival management has shifted toward electronic systems, supervisory practices and archival audits remain largely manual and administrative. The study aims to analyze the effectiveness of internal archival supervision, identify implementation challenges to strengthen supervisory systems. This research employed a qualitative descriptive approach using interviews, observations, and documentation involving archivists, government officials, Internal Archival Audit Reports (LAKI) verifiers, and archival from several Regional Government Organizations (OPD). Secondary data were obtained from LAKI, archival regulations, and related literature. Data were analyzed using the Miles and Huberman interactive model. The findings show that internal archival supervision has not adapted optimally to digital transformation. Based on George R. Terry’s supervisory theory, the stages of setting standards, measuring performance, and correcting deviations are still dominated by administrative and compliance-oriented approaches. Although several agencies have implemented SRIKANDI, supervision is still conducted manually through physical document verification and conventional audit procedures. Consequently, monitoring and evaluation remain fragmented and less effective in providing real-time control. Major obstacles include limited digital integration, insufficient archival human resources, weak follow-up mechanisms, and inadequate institutional support. The study concludes that digital archival transformation must be accompanied by integrated digital supervisory systems, competency enhancement, and institutional strengthening to support adaptive and sustainable archival governance.